Experimental reconstruction of monsoon drought variability for Australasia using tree rings and corals - Rosanne D'Arrigo; Patrick Baker; Jonathan Palmer; Kevin Anchukaitis; Garry Cook (Geophysical Research Letters)
An experimental reconstruction uses three well‐dated, annually‐resolved proxies from Australasia (0–40°S, 95–155°E) to provide large‐scale information on Sep–Jan Australasian monsoon variability based on the Palmer Drought Severity Index (PDSI) for 1787–2002. The proxies are: (1) a ring width chronology of Callitris intratropica for northern Australia (1847–2006); (2) a tree‐ring and coral–based reconstruction of the Oct–Nov PDSI (1787–2003) for Java, Indonesia; and (3) a rainfall reconstruction for northeastern Australia (1631–2002) based on Great Barrier Reef coral luminescence. All three proxies show considerable explanatory value for reconstructing monsoon rainfall variability over much of Australia and environs, which will improve as additional records become available. The success of this “proof of concept” experiment largely reflects the highly significant, spatially‐coherent correlations between austral spring and summer PDSI, Australasian climate and ENSO.